Speed Control of DC Motor Using Interval Type-2 Fuzzy Logic Controller - Acikgoz, Hakan (Prof. Dr. Ismail SARITAS, 2018)
Direct current (DC) motors are widely used for speed control and position control in industry. The simplicity of DC motor speed control is also the main reason for its widespread use. Recently, in parallel with rapid developments in power electronics, microprocessors and semiconductor materials, many control structures are designed for DC motors. In this study, the speed control of the DC motor is carried out using the Matlab/Simulink package program. Type-2 Fuzzy Logic controller (T2FLC) which has efficient performance in modelling uncertainties is proposed for the speed control of DC motor. The classical PI controller and Type-2 Fuzzy Logic controller (T2FLC) are applied to the speed control unit of the DC motor. Simulation studies have also been realized for the designed DC motor model under the same conditions. The results obtained from the classical PI controller and T2FLC have been examined and compared to disturbances such as tracking reference speeds and load changes. According to the obtained simulation results, it has been observed that T2FLC has better results than the classical PI controller in whole conditions.Â